PENGARUH LATIHAN MOTORIK HALUS TERHADAP PENINGKATAN KEMAMPUAN MENULIS PADA ANAK AUTIS DI SEKOLAH LUARBIASA (SLB) NEGERI 1 ARGAMAKMURBENGKULU UTARA - fus, Yenni Fusfitasari; Anter Dioni Putra; Nurman Jaya (LPPM STIKES BHAKTI HUSADA BENGKULU, 2025)
Fine motor training can be an approach to improving writing skills in autistic children through stimulation of the small muscles of the hand. A research problem is the persistence of autistic children who experience a decline in writing ability. The purpose of this study was to determine the effect of fine motor training on improving writing skills in autistic children at the State Special School (SLB) 1 Argamakmur, North Bengkulu. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 10 autistic children attending SLB Negeri 1 Argamakmur, North Bengkulu. The intervention, in the form of fine motor training, was administered for two weeks. Measurements were taken before and after the intervention and then analyzed using the Wilcoxon Signed Rank Test. The results showed that the average writing ability score before the intervention was 3.20, and after the intervention it increased to 4.50. The Wilcoxon Signed Rank Test yielded a p-value of 0.004 (p < 0.05), indicating that the improvement was statistically significant and not a random occurrence, but rather a tangible result of the fine motor training provided. Suggestions for fine motor training can be used as a supporting strategy in learning at special needs schools or as support at home. Keywords: Fine Motor Training, Writing, Autism